Clinical profile of 102 patients with oral lichen planus in Thailand - Kaomongkolgit, Ruchadaporn (J Clin Exp Dent, 2019)
BACKGROUND: Oral lichen planus (OLP) is a chronic inflammatory disease of the skin and mucous membrane presented with various clinical appearances. The aim of the present study was to elucidate the clinical profile of patients with OLP. MATERIAL AND METHODS: The dental records of 102 patients who visited Oral Medicine Clinic, Dental Hospital, Naresuan University during 2002-2018 were retrospectively reviewed. RESULTS: There were 75 (73.5%) women and 27 (26.5%) men, giving a female to male ratio of 2.8:1. The age of OLP patients ranged 20-81 years old with the mean age of 56.4 ± 13.2 years old. Seventy-eight patients (76.5%) had the history of systemic diseases and hypertension was the predominantly one. Most patients were non-smokers (98%), non-drinkers (86.3%) and non-betel nut chewers (98%). The atrophic form (93.1%) was the most common OLP. The lesions were mainly symptomatic (92.2%) and involved multiple locations (67.6%) where the buccal mucosa (79.4%) primarily affected. Only 2% were extraoral lesions detected on the skin. Patients had no family history of OLP or malignant transformation. Ninety-one patients (89.2%) were treated with topical steroid and only 4 patients were prescribed a combination of tropical and systemic steroid. CONCLUSIONS: The results of the study indicated that most of characteristics are in accordance with previous studies. Since, OLP is a chronic inflammatory oral mucosal disease with high recurrence rate, early detection, accurately diagnosis, and long-term follow-up are necessary to evaluate the exacerbation and malignant transformation. Key words:Clinical profile, demographic, oral lichen planus, retrospective study.